Analisis Perhitungan Harga Pokok Produksi Menggunakan Metode Job Order Costing Pada CV Lebong Kreasi Palembang - Anjelin Vio Julia; Eka Jumarni Fithri; Muhammad Husni Mubarok (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The main objective of this report is to evaluate the current cost of goods manufactured calculation, analyze the unaccounted costs in the cost of goods manufactured, and provide recommendations for improving the cost of goods manufactured calculation process. The research method involves collecting primary data through surveys and interviews with company staff. The data sample includes information on the use of material costs, labor, fixed asset lists, and the calculation of the cost of goods produced for hard cover invitations and bairut gold cover yasin books during February 2023. The results of the analysis show that the company has not made a correct classification of the elements of the cost of goods manufactured and has not included some costs in the cost of goods manufactured. In addition, the charging of factory overhead costs has not been applied properly. Therefore, recommendations are suggested for the company to carry out proper classification of the elements of cost of goods manufactured, Include costs related to electricity bills and depreciation of tangible assets in the cost of goods manufactured budget or overhead costs.